The future of responsible company what we've learned from Patagonia's first 50 years - Stanley, Vincent; Chouinard, Yvon 1938- (Tantor Media, Inc., 2024)
Vincent Stanley, Patagonia's director of philosophy, with Yvon Chouinard, founder and former owner of Patagonia, draws on fifty years' experience to challenge all business owners and leaders to rethink their businesses in a time of cultural and climate chaos. Patagonia has been recognized as much for its groundbreaking environmental, social practices as for the quality of its clothes. In an unprecedented action, in 2022, the Chouinard family gave their company away, converting ownership to a structure of trusts and nonprofits, so that all the profits from the company can be used to protect our planet and work to reverse climate chaos. In this frank account, Stanley with Chouinard recounts how the company and its culture gained the confidence to make its work progressively more responsible, and to ultimately challenge other companies to do the same. The authors describe the current impact of manufacturing, commerce, and traditional capitalism on the planet's natural systems and human communities, and how that impact is forcing business to change its ways. This book shows companies how to reduce the harm they cause, improve the quality of their business, and provide the kind of meaningful work everyone seeks. It concludes with specific, practical steps every business can undertake, as well as advice on what to do, in what order.
Online resource; title from title details screen (O'Reilly, viewed December 10, 2024)
Keywords: Patagonia, Inc -- History; Sport clothes industry -- California; Business enterprises -- Environmental aspects -- California; Environmental responsibility -- California; Vêtements de sport; Industrie; Californie; Entreprises; Aspect de l'environnement; Californie; Responsabilité environnementale; Californie; Audiobooks; Livres audio